The Importance of Mental Functions and Autobiographical Memory in the Development of Identity and Life Story in Adolescence: Their Role in Preventing Identity Diffusion, Aggressiveness And Depression Among Adolescents - Seri, Lucia; Montebarocci, Ornella (Journal of Child and Adolescent Psychiatry, 2024)
The structuring of one’s own identity is a fundamental and demanding evolutionary task of adolescence. The positive resolution of this task, that is the acquisition of a healthy and integrated identity, is closely linked to adolescents’ ability to develop one’s own Life Story, namely an internalized and evolving self-story. The structuring of one’s own identity, which is the foundation of positive development, requires adolescents to develop a good level of mental functioning and access to autobiographical memory. This work aims to deepen the importance of mental functions and autobiographical memory in the development of adolescents’ identity and life story and, accordingly, in preventing identity diffusion, aggressiveness and depression among adolescents. Specifically, given their relevance in relation to this, it has been decided to examine the mental functions of 1) Differentiation and Integration, 2) Mentalization and Reflexive function and 3) Meaning and directionality and the Self defining memories, a particular class of autobiographical memories.
Keywords: Identity; Life Story; Adolescence; Self-defining memories; Mental functions; Overgeneral autobiographical memory